Au–Pd bimetallic nanoparticles anchored on α-Fe2O3 nonenzymatic hybrid nanoelectrocatalyst for simultaneous electrochemical detection of dopamine and uric acid in the presence of ascorbic acid. Issue 15 (23rd March 2016) - Sumathi, C.; Venkateswara Raju, C.; Muthukumaran, P.; Wilson, J.; Ravi, G.
Abstract : We have found that magnetic α-Fe2 O3 nanocubes exhibit an intrinsic catalytic activity toward the electrochemical sensing of dopamine (DA) and uric acid (UA) in the presence of ascorbic acid. Abstract : We have found that magnetic α-Fe2 O3 nanocubes exhibit an intrinsic catalytic activity toward the electrochemical sensing of dopamine (DA) and uric acid (UA) in the presence of ascorbic acid. Au–Pd bimetallic nanoparticles, which act as efficient signal amplifiers, can be attached to the surface of α-Fe2 O3 particles to further enhance the catalytic electrochemical signals. The one-step synthesized α-Fe2 O3 @Au–Pd hybrid nanostructure shows significantly well-separated oxidation peaks with enhanced peak currents of DA and UA. We then demonstrated the use of this nonenzymatic nanoelectrocatalyst for individual detection, and the linear responses of DA and UA were in the concentration ranges of 100 nM −1 mM and 1 μM −1 mM with detection limits of 1.34 × 10 −10 M and 1.8 × 10 −6 M (S/N = 3 σ /b), respectively. For simultaneous detection, the same detection ranges were retained with significantly lower detection limits of 1.38 × 10 −11 M and 597 nM, respectively. The fabricated sensor was finally applied in selectivity tests for the detection of DA and UA with satisfactory results. The practical analytical utility was illustrated by selective measurements of human urine, serum and pharmaceutical drugs without any preliminary treatment.